Perilaku Konsumen Dalam Perspektif Islam - Annisa, Neng Nur (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2023)
Human resources and the satisfaction of demands or consumption are inextricably linked in daily life. Islamic economics gives an overview of consumption that is permitted and required by Islamic teachings, which are governed by the Shari'ah's laws, as well as providing guidance in this area. Depending on the behavior when utilizing the item or commodity, something that is truly permitted to be used or consumed can turn into something that is against the Shari'a. It can be said that Islamic consumerism is replete with spiritual ideals that subtly advise people to refrain from overindulging and focus on maintaining their well-being rather than their pleasure and satisfaction.